Olympic pride, American prejudice : the untold story of 18 African Americans who defied Jim Crow and Adolf Hitler to compete in the 1936 Berlin Olympics - Draper, Deborah Riley; Thrasher, Travis, 1971-; Underwood, Blair (Atria Books, 2020)
Set against the turbulent backdrop of a segregated United States, sixteen black men and two black women are torn between boycotting the Olympic Games in Nazi Germany or participating. If they go, they would represent a country that considered them second-class citizens and would compete amid a strong undercurrent of Aryan superiority that considered them inferior. Yet, if they stayed, would they ever have a chance to prove them wrong on a global stage? To be better than anyone ever expected? Five athletes, full of discipline and heart, guide readers through this harrowing and inspiring journey. There<U+2019>s a young and sometimes feisty Tidye Pickett from Chicago, whose lithe speed makes her the first African American woman to compete in the Olympic Games; a quiet Louise Stokes from Malden, Massachusetts, who breaks records across the Northeast with humble beginnings training on railroad tracks. We find Mack Robinson in Pasadena, California, setting an example for his younger brother, Jackie Robinson; and the unlikely competitor Archie Williams, a lanky book-smart teen in Oakland takes home a gold medal. Then there<U+2019>s Ralph Metcalfe, born in Atlanta and raised in Chicago, who becomes the wise and fierce big brother of the group. Drawing on over five years of research, Draper and Thrasher bring to life a timely story of perseverance and the will to beat unsurmountable odds. From burning crosses set on the Robinsons<U+2019>s lawn to a Pennsylvania small town on fire with praise and parades when the athletes return from Berlin, Olympic Pride, American Prejudice is full of emotion, grit, political upheaval, and the American dream. Capturing a powerful and untold chapter of history, the narrative is also a celebration of the courage, commitment, and accomplishments of these talented athletes and their impact on race, sports and inclusion around the world.